Faktor-Faktor Yang Mempengaruhi Kinerja Keuangan: Studi Empiris Pada Perusahaan Di Indonesia - Putri Hapsari, Denny; Kurnia, Denny; Arifin, Wiwin (Universitas Serang Raya, 2024)
RETURN ON EQUITY AS A TOOL FOR MEASURING FINANCIAL PERFORMANCE AND INFLUENCE FACTORS: EMPIRICAL STUDY OF COMPANIES IN INDONESIA Abstract The aim of this research is to identify variables that influence the financial performance of companies in Indonesia, especially manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2022. Green accounting, environmental performance, corporate social responsibility, and sales growth are variables. independent used. This research is quantitative because it uses secondary data. 26 companies were taken as samples during 4 years of observation, resulting in a total of 104 samples for research. The research results show by multiple linear regression analysis that sales growth and environmental performance greatly influence financial performance, which is measured through Return On Equity (ROE). In contrast, corporate social responsibility (CSR) and green accounting do not affect financial performance. Keywords: Green accounting; Environmental Performance; Corporate Social Responsibility (CSR) CSR; Sales Growth; Financial performance